Memory and Imagination in Film - Lombardo, P. author. aut Link
IX, 244 p.
Keywords: Inspired by Baudelaire's art criticism and contemporary theories of emotions, and developing a new aesthetic approach based on the idea that memory and imagination are strongly connected, Lombardo analyzes films by Scorsese, Lynch, Jarmusch and Van Sant as imaginative uses of the history of cinema as well as of other media.